PEMANFAATAN POJOK BACA DALAM GERAKAN LITERASI SEKOLAH - Rasidi, Muhamad Ahyar; Susetiyo, Ari (Nidhomiyyah: Jurnal Manajemen Pendidikan Islam, 2023)
This study discusses the reading corner in the implementation of the school literacy movement, the current era makes reading activities seem boring. Pserta students need to be given a container for them to learn, classroom corner teredia books for them to read. both elementary schools and those in madrasah Ibtida'iyah, theoretical studies. The Data obtained came from rfereni-references about the reading corner, school literacy movement,the results of Theoretical Studies in this study of course the existence of a reading corner that makes students interested in peseta, with the reading corner makes students more respect for time, students become more insightful, reading corner aims to build interest from students, and the next value is that students have a noble character because with more reading, the smarter, then make students get achievements.